Refleksi Pemikiran Multikulturalisme bagi Dakwah - Ellyda Retpitasari; Luluk Fikri Zuhriyah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This paper aims to discuss multiculturalism thinking from Europe and Asia, such as Bikhu Parekh, Daniel Conjanu, and Charles Taylor. Multiculturalism thinking is explored for the sake of Da'wa, or it can be called as multiculturalism preaching. This study uses literature review, and analysis of multiculturalism phenomena in the city of Surabaya. These thinkers used a number of approaches in terms of recognition politics, new identity politics, political equality with dignity, politics of difference, accommodative multiculturalism, and pragmatism. In the analysis of the Da'wa approach is divided into two, namely the structural approach and cultural approach. The structural approach refers to politics that encompasses politics of recognition, politics of new identity, politics of equality with dignity, and politics of difference. As for the cultural approach, it encompasses accommodative multiculturalism and pragmatism. Through this multicultural preaching approach it becomes an offer in overcoming the problems of preaching in multicultural societies.